2015
DOI: 10.1111/1556-4029.12814
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Label Prescribing by Psychiatrists: What is the Practitioner's Liability?

Abstract: In psychiatry, the molecules available and the dosages recommended when a drug receives marketing authorization are not always adequate to treat patients with major behavioral disturbances. Off-label prescribing is frequent in this context, with regard to the indications and the dosages given as well as to the drug combinations used. However, if complications or death occur, the practitioner's liability may be engaged. The authors report three deaths attributed to off-label prescribing in psychiatry and which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…12,13,[16][17][18][19][20] In addition to these concerns, the provision of PrEP to youth may present unique challenges related to the ability of minor adolescents to access PrEP without parental consent. 21 Clinicians may also be wary of the possible legal consequences of prescribing PrEP off-label to adolescents, 22,23 which could negatively impact clinician willingness to recommend or prescribe this method to youth. To optimize PrEP uptake by adolescents, it is critical to understand clinicians' attitudes about prescribing PrEP.…”
mentioning
confidence: 99%
“…12,13,[16][17][18][19][20] In addition to these concerns, the provision of PrEP to youth may present unique challenges related to the ability of minor adolescents to access PrEP without parental consent. 21 Clinicians may also be wary of the possible legal consequences of prescribing PrEP off-label to adolescents, 22,23 which could negatively impact clinician willingness to recommend or prescribe this method to youth. To optimize PrEP uptake by adolescents, it is critical to understand clinicians' attitudes about prescribing PrEP.…”
mentioning
confidence: 99%
“…As a recommendation, patients should be properly educated about every off‐label drug use, supporting evidence, the risk of toxicities and financial impact on treatment costs . Obtaining informed consent was highly recommended by participants to safeguard patient autonomy leading to better healthcare decision with off‐label use and to prevent any future legal liabilities . The oncology practitioners generally agreed upon on moderate enhancement in the overall quality of life than specific survival gains with off‐label drug use.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured guide was developed based on a comprehensive review of the literature and the practices of OLDP reported previously [14,[21][22][23][24][25]. The guide was intended to explore the respondent's knowledge about OLDP, their concerns about its safety and efficacy, the probability of ADRs and their current practices of OLDP.…”
Section: Development Of Interview Guidementioning
confidence: 99%